Respuesta :

frika

Answer:

[tex]f^{-1}(g^{-1}(x))=\dfrac{1}{5}x+2.[/tex]

Step-by-step explanation:

1. If [tex]g(x)=x-4,[/tex] then

[tex]y=x-4,\\ \\x=y+4.[/tex]

Change y into x and x into y:

[tex]y=x+4,\\ \\g^{-1}(x)=x+4.[/tex]

2. If [tex]f(x)=5x-6,[/tex] then

[tex]y=5x-6,\\ \\5x=y+6,\\ \\x=\dfrac{y+6}{5}.[/tex]

Change y into x and x into y:

[tex]y=\dfrac{x+6}{5},\\ \\f^{-1}(x)=\dfrac{x+6}{5}.[/tex]

3. Find [tex]f^{-1}(g^{-1}(x)):[/tex]

[tex]f^{-1}(g^{-1}(x))=f^{-1}(x+4)=\dfrac{(x+4)+6}{5}=\dfrac{x+10}{5}=\dfrac{1}{5}x+2.[/tex]